From sounds to structures: beyond the veil of Maya Studies in generative grammar ;, 135./ edited by Roberto Petrosino, Pietro Cerrone, Harry van der Hulst. - Petrosino Roberto; Cerrone Pietro; Hulst Harry van der (2018)
English. Includes bibliographical references and index. "The term 'Maya' refers to our sensory perception of the world and to a superficial reality that we must look beyond to find the inner reality of things. Applied to the study of language, we perceive sounds, a superficial reality, and then we seek structures, the underlying reality in what we call phonology, morphology, and syntax. The papers collected in this volume reflect the research interests and influence of Andrea Calabrese"-- The status of Italian glides in the syllable / Stefano Canalis -- The phonology and phonetics of laryngeal stop contrasts in Assamese / Hemanga Dutta and Michael Kenstowicz -- The phonetics-phonology relationship in the neurobiology of language / Mirko Grimaldi -- Metaphony with unary elements / Harry van der Hulst -- Many sons of Aodh : tracing multiple outcomes of the Scottish and Irish clan name Macaoidh/a Haodha / Elizabeth J. Pyatt -- Disharmony and decay : Itelmen vowel harmony in the 20th century / Jonathan David Bobaljik -- Deriving morphophonological (mis)applications / David Embick and Kobey Shwayder -- Distribution of falling tones in Mabaan / Irina Monich -- Vedic Sanskrit accentuation and readjustment rules / J. Joseph Perry and Bert Vaux -- Allomorphy of Italian determiners at the morphology-phonology interface / Roberto Petrosino -- Diachronic and synchronic aspects in the expression of temporal distance in the past : a process of grammaticalization in Italian compared with other Romance languages and English / Paola Beninc̀a, Mariachiara Berizzi, Laura Vanelli. 1 online resource